2000
DOI: 10.1038/79558
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazinamide inhibits the eukaryotic-like fatty acid synthetase I (FASI) of Mycobacterium tuberculosis

Abstract: Tuberculosis treatment is shortened to six months by the indispensable addition of pyrazinamide (PZA) to the drug regimen that includes isoniazid and rifampin. PZA is a pro-drug of pyrazinoic acid (POA) (ref. 3), whose target of action has never been identified. Although PZA is active only against Mycobacterium tuberculosis, the PZA analog 5-chloro-pyrazinamide (5-Cl-PZA) displays a broader range of anti-mycobacterial activity. We have found that the eukaryotic-like fas1 gene (encoding fatty acid synthetase I,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
187
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 231 publications
(198 citation statements)
references
References 31 publications
10
187
0
1
Order By: Relevance
“…The mycobacterial FASII system is incapable of de novo fatty acid synthesis but instead elongates acyl primers (C 16 -26 ) to larger mycolic acid intermediates (38). For this reason, purified KasA and KasB activities were initially tested using C 16:0 acyl substrates.…”
Section: Figmentioning
confidence: 99%
“…The mycobacterial FASII system is incapable of de novo fatty acid synthesis but instead elongates acyl primers (C 16 -26 ) to larger mycolic acid intermediates (38). For this reason, purified KasA and KasB activities were initially tested using C 16:0 acyl substrates.…”
Section: Figmentioning
confidence: 99%
“…It has been shown that acid pH enhances the uptake and accumulation of POA in M. tuberculosis, which has been shown to have a defective ef¯ux mechanism for POA [15]. While the target of POA is thought to be fatty acid synthesis pathway 1 [16], POA as a weak acid could potentially kill tubercle bacilli through recycling of POA leading to de-energised membrane as a possible mechanism of action [17].…”
Section: Introductionmentioning
confidence: 99%
“…80,81 The major mechanism of PZA resistance in Mtb described in the literature is mutation in its activator gene pncA [82][83][84][85][86][87][88][89] . In an effort to overcome resistance and enhancing PZA activity, scientists have derivatized pyrazinamide in different ways.…”
Section: Isoniazid As Targetmentioning
confidence: 99%